Icariin inhibits autophagy and promotes apoptosis in SKVCR cells through mTOR signal pathway - Jiang, Shaoyan; Chang, Hong; Deng, Shaojie; Fan, Danyi (Cellular and Molecular Biology, 2018)
Autophagy is a conserved biological process, which is regulated by mTOR pathway and is reported to be a self-protective process of cancer cells to counteract apoptosis. Icariin is an active flavonoid that is reported to inhibit autophagy. In this study, we investigated whether Icariin could induce a reduction of cell proliferation by inhibiting autophagy. SKVCR cells, which are resistant to vincristine, were used for the investigation. We used CCK8 test and flow cytometry assay to study the effects of Icariin on cell proliferation, cell apoptosis and cell circle. We performed transmission electron microscope (TEM), immunohistochemical assay and western blotting assay to study the level of autophagy after Icariin treatment. Finally, we investigated whether the mTOR pathway is a target of Icariin by using mTOR inhibitor rapamycin and detected autophagy and apoptosis via flow cytometry assay, TEM, immunohistochemical assay and western blotting assay. Decreased proliferation and increased apoptosis was observed after Icariin treatment in SKVCR cells, together with decreased level of autophagy. Application of rapamycin could reverse the anti-autophagic and pro- apoptotic effect of Icariin. Icariin can inhibit autophagy and promote apoptosis in SKVCR cells by activating mTOR signal pathway. Icariin attenuates tumorigenesis by inhibiting autophagy and inducing apoptosis.